Reader's Digest Complete Guide to Sewing (USA Reader's Digest Association, 1978)
Covers tools, patterns, fitting methods, sewing basics, tailoring techniques, sewing for the home, and sewing projects
Includes index
Keywords: Applied Sciences (3GdYdhe GdJWHjbjIs; Sewing; Dressmaking; General